2021
DOI: 10.1109/led.2021.3055287
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Orientation Misalignments on Black Phosphorus Ultrascaled Field-Effect Transistors

Abstract: Two-dimensional materials with strong bandstructure anisotropy such as black phosphorus (BP) have been identified as attractive candidates for logic application due to their potential high carrier velocity and large density-of-states. However, perfectly aligning the source-to-drain axis with the desired crystal orientation remains an experimental challenge. In this paper, we use an advanced quantum transport approach from first-principle to shed light on the influence of orientation misalignments on the perfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Nevertheless, a region where the current is almost insensitive to the misalignment angle can be expected in all cases, as suggested Klinkert et al (2021). If 2-D materials should replace Si as the channel of future field-effect transistors, they should be used during several consecutive technology nodes.…”
Section: Novel 2-d Materialsmentioning
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, a region where the current is almost insensitive to the misalignment angle can be expected in all cases, as suggested Klinkert et al (2021). If 2-D materials should replace Si as the channel of future field-effect transistors, they should be used during several consecutive technology nodes.…”
Section: Novel 2-d Materialsmentioning
confidence: 92%
“…For example, it is well-known in BP that transport along the Γ-Y axis is (much) less efficient than along Γ-X (Xia et al (2014)). Using the proposed MLWF+NEGF approach, we found in Klinkert et al (2021) that orientation misalignments up to 50 • from the ideal case do not significantly alter the ON-state current of BP transistors, with almost negligible performance loss up to a misalignment angle of 20 • . This means that I ON does not linearly decrease as a function of the misalignment angle, but rather first stays constant up to 20 • , slightly decreases up to 50 • , and finally rapidly drops.…”
Section: Novel 2-d Materialsmentioning
confidence: 97%
“…Klinkert et al used a coupled DFT-NEGF approach to investigate the orientation misalignments and their impact on the performance of black phosphorus FETs [337]. N-and p-type configurations were investigated including six alignment angles.…”
Section: D Fetsmentioning
confidence: 99%
“…BP applications as the field-effect transistors (FETs) has been extensively studied [16][17][18][19][20][21][22][23][24][25]. The ballistic performance limit of monolayer BP FETs has also been studied [17,18,26,27]. They have reported high on current and high carrier mobility along the armchair direction due to lighter carrier mass.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [27] have experimentally studied a 12.5 nm thick BP FET and they have found that interface engineering with high quality HfLaO dielectrics and the channel oriented along the armchair direction can provide high on-state current up to 1.6 mA µm −1 with a ballistic limit up to 79%. Klinkert et al [26] have studied the misalignment between the preferred crystallographic axis (the one with the lowest effective mass) and the source-drain axis. They have found that the on-state current is decreased by only 30% for up to the misalignment angle of 50 • from the optimal direction.…”
Section: Introductionmentioning
confidence: 99%